Attraction of female and male oriental fruit flies to conspecific males and mating competition following consumption of zingerone and ethyl vanillate. - Hee, Alvin K.W.; Wee, Suk-Ling; Tan, Keng-Hong; Ritsuo, Nishida (2011)
Floral volatiles containing methyl eugenol, raspberry ketone or zingerone (Z) are known to modulate interactions between Bulbophyllum orchids and Bactrocera fruit flies. Recently, flowers of Bulbophyllum elevatopunctatum containing ethyl vanillate (EV) as one of the volatile component, was observed to attract fruit flies, which the probe on floral lip, petals and sepals. But the effects of consumption of the floral chemical on the behavioural ecology of the fruit fly are not known. We studied the attraction of virgin females and males of the Oriental fruit fly, Bactrocera dorsalis, to conspecific males fed with either Z or EV in a wind tunnel. Concomitant with decreasing light intensity, males fed with either Z attracted significantly higher numbers of conspecific males and females during the courtship period at dusk. When groups of attractant-deprived, Z-and EV-fed males were released together into a large field cage containing virgin females, significantly higher numbers of the Z- and EV-fed males were caught in copula than the sttractant-deprived males. This suggests that both Z and EV may act as precursors to the male pheromone that promotes the mating competitiveness.